Fennoscandian strain rates from BIFROST GPS: A gravitating, thick-plate approach - Scherneck, Hans-Georg; Lidberg, Martin; Haas, Rüdiger; Johansson, Jan; Milne, Glenn A. (Journal of Geodynamics, 2010)
The aim of this investigation is to develop a method for the analysis of crustal strain determined bystation networks that continuously measurements of Global Navigation Satellite Systems (GNSS). Themajor new ingredient is that we require a simultaneous minimum of the observation error and theelastic and potential energy implied by the deformation.The observations that we analyse come from eight years worth of daily solutions from continuousBIFROST GPS measurements in the permanent networks of the Nordic countries and their neighbours.Reducing the observations with best fitting predictions for the effects of glacial isostatic adjustment (GIA)we find strain rates of maximum 5 nano/yr in the interior of the rebound area predominantly as arealstrain. The largest strain rates are found in the Finnmarken area, where however the GNSS networkdensity is much lower than in the central and southern parts.The thick-plate adjustment furnishes a simultaneous treatment of 3-D displacements and the ensuingelastic and potential energy due to the deformation. We find that the strain generated by flexure due toGIA is important. The extensional regime seen at the surface turns over into a compressive style alreadyat moderated depth, some 50 km.